Arctique : opportunités, enjeux et défis - Quillérou, Emmanuelle; Jacquot, Mathilde; Cudennec, Annie; Bailly, Denis; Choquet, Anne; Zakrewski, Laure (CCSD, 2019)
International audience The Arctic is pictured in the collective mind as a white and frozen desert, with only a few polar bears, explorers and Eskimos sprinkled around. It is, however, inhabited by very diverse people, and several industries are well established in the Arctic, through the Arctic, or at the periphery of the Arctic Circle. Receding and thinning sea ice because of climate change opens up access to natural resources, shipping routes and touristic areas, thereby providing new opportunities for economic development in the Arctic. The potentially high rewards are extremely attractive, but at high financial, environmental and social costs in a high-risk environment. Some stakeholders have started securing access to Arctic resources, sowing the seeds for a ‘cold rush’. Despite increased prominence in the media of Arctic bonanza, sometimes closer to myth than reality, such ‘cold rush’ does not seem to have fully materialised yet, slowed down by high investment costs and legal considerations, as well as high diplomatic, political and social sensitivity. The main political challenge ahead is for decision-makers to successfully reconcile highly contrasted perspectives and interests in the Arctic, from the local to the international levels, by building up existing institutional capacity at the pace of economic development. There is certainly strong potential for creating shared economic wealth and well-being, with a fair distribution of Arctic benefits. Choices for economic development, coordination and cooperation by Arctic countries and private actors in the next few years will shape the Arctic of tomorrow. L'Arctique est, dans l'esprit collectif, un désert blanc et glacé, associé aux ours polaires et aux explorateurs. On trouve pourtant des populations et plusieurs activités économiques établies en Arctique, à travers l'Arctique, ou à la périphérie du cercle polaire arctique, lui conférant de multiples visages. La fonte de la banquise induite par le changement climatique a rouvert la question de l'accès ...